تطوير وسيلة تعليم اللغة العربية على مادة البيانات الشخصية باستخدام كانفا وبيكسلاب لطلاب الصف العاشر: Pengembangan Media Pembelajaran Bahasa Arab Materi Al Bayanat Asy Syakhshiyyah Menggunakan Canva dan Pixellab pada Siswa Kelas X - Kadir, Huron Mahsyurah; Andi Arif Pamessangi (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
This study aims to identify the development process and the validity level of the developed product. This type of research is research and development (R&D) by adapting the 4D development model, which consists of four stages: define, design, develop, and disseminate. The subjects of this study are tenth-grade students of MAN Palopo. Data collection techniques include observation, interviews, validation sheets, student response questionnaires, and documentation. The data were analyzed using qualitative and quantitative data analysis techniques. The result of this development research is an Arabic learning media on the topic of